Exploring the Role of Nanoparticles in Amphotericin B Delivery - Zaioncz, Soraia; Maissar Khalil, Najeh; Mara Mainardes, Rubiana (Current Pharmaceutical Design, 2017)
Amphotericin B (AmB) is the drug of choice in the treatment of invasive fungal infections and visceral leishmaniasis. Although AmB has a higher selectivity for ergosterol (present in fungi and Leishmania spp. membrane) than for cholesterol, mammalian cells are affected by AmB, mainly in its oligomeric aggregated form, resulting in side effects, especially nephrotoxicity. The development of nanotechnology-based drug delivery systems for AmB is a promising avenue since nanoparticles have the ability to target drugs to the infected cells, and their prolonged drug release profile permits longer contact between the drug and the fungi/parasite. In this review, we made an overview about nanoparticles as colloidal carriers for AmB, including polymeric-based nanoparticles, protein-based nanoparticles and solid lipid-based nanoparticles with respect to their application for the treatment of invasive fungal infections and leishmaniasis.
Keywords: biodegradable polymers